Sexual awareness, high-risk sexual behaviors and HIV testing: a cross-sectional survey among university students in Xuzhou, Jiangsu - Li, Hualing; Wu, Qi; Li, Qinghan; Gao, Enze; Yin, Dehui (Frontiers in Public Health, 2025)
BackgroundAs societal dynamics evolve, a noticeable trend has emerged indicating that Chinese adolescents are engaging in sexual activities at increasingly younger ages. This demographic is therefore identified as a crucial group for initiatives aimed at the prevention and control of HIV. The primary objective of this study is to investigate the psychological and behavioral characteristics of gender (male and female) college students in Xuzhou. It will analyze the key factors that influence their sexual behaviors, particularly those associated with high-risk sexual practices, and explore the determinants that affect their willingness to participate in HIV testing. This research aims to establish a scientific foundation for enhancing college students’ understanding of HIV prevention and control strategies, ultimately contributing to a reduction in the risk of infection.MethodsThis research employed a cross-sectional survey design to distribute an anonymous questionnaire to a sample of 4,193 college students from four universities in Xuzhou. The questionnaire included items related to demographic characteristics, gender-specific psychological perceptions, sexual behavior patterns, and HIV testing status. Univariate analysis was conducted using chi-square tests, while logistic regression was utilized to examine the interactive effects of multiple variables.ResultsIn the studied population, males comprised 44.0%, while females accounted for 56.0%, with medical students representing 55.8% of the sample. The survey revealed that 9.3% of students reported having sexual experience, and 3.27% engaged in high-risk sexual behaviors, with a notably higher prevalence among males compared to females. Multivariate analysis identified several key factors influencing high-risk sexual behavior, including gender, academic grade level, monthly expenditure, sexual orientation, and dating experience. Females were found to have a lower likelihood of engaging in high-risk sexual behavior compared to their male counterparts (OR = 0.72, 95% CI = 0.122–1.623). In contrast, the risk was significantly higher for homosexual (OR = 3.12, 95% CI = 1.607–6.052) and bisexual (OR = 2.64, 95% CI = 1.289–5.423) students. Furthermore, upperclassmen and those with multiple dating experiences exhibited correspondingly increased risks. The prevalence of HIV testing within the population was 4.6%, with influencing factors including gender, whether the student is an only child, ethnicity, sexual orientation, dating experience, and previous sexual behavior. Notably, the willingness to undergo testing was lower among females, ethnic minorities, and individuals identifying as bisexual.ConclusionThis research examines the current conditions and characteristics of college students in Xuzhou concerning sexual psychology, sexual behavior, and HIV testing. It is advisable for universities to establish focused sexual health education and HIV prevention programs that are specifically designed to address the unique attributes of various student demographics, with particular attention to high-risk groups. Additionally, institutions should ensure the availability of accessible testing services, create a robust psychological support framework, reduce the risk of HIV transmission, and promote a healthy and safe campus atmosphere.